TEKNOLOGI INFORMASI SEBAGAI PEMODERASI PADA FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN - Widhiastuti, Ni Luh Putu; Sagung Oka Pradnyawati (Faculty of Economics and Business University of Mataram, 2023)
Village Credit Institutions (LPD) have an essential role in the economy of rural communities. This research examines the influence of education level, professionalism, leadership ethics, and the function of the supervisory body on the quality of financial reports by moderating the use of information technology in LPDs in Denpasar City. Ninety-six respondents were selected based on non-probability sampling and analyzed using moderated regression analysis (MRA). The test results show that the level of education, professionalism and use of information technology positively influence the quality of financial reports. However, leadership ethics and the function of the supervisory body have no significant influence. Information technology can moderate the relationship between education level and professionalism in the quality of financial reports. However, information technology is not significant in moderating leadership ethics and the function of supervisory bodies on the quality of financial reports. This research implies the critical role of supervision through an internal control system and better governance in LPD management.